Enriched continental flood basalts from depleted mantle melts : modeling the lithospheric contamination of Karoo lavas from Antarctica - Heinonen, Jussi S.; Luttinen, Arto V.; Bohrson, Wendy A. (Contributions to Mineralogy and Petrology, 2016)
Continental flood basalts (CFBs) represent large-scale melting events in the Earth’s upper mantle and show considerable geochemical heterogeneity that is typically linked to substantial contribution from underlying continental lithosphere. Large-scale partial melting of the cold subcontinental lithospheric mantle and the large amounts of crustal contamination suggested by traditional binary mixing or assimilation-fractional crystallization models are difficult to reconcile with the thermal and compositional characteristics of continental lithosphere,however. The well-exposed CFBs of Vestfjella, western Dronning Maud Land,Antarctica, belong to the Jurassic Karoo large igneous province and provide a prime locality to quantify mass contributions of lithospheric and sublithospheric sources for two reasons: 1) recently discovered CFB dikes show isotopic characteristics akin to mid-ocean ridge basalts, and thus help to constrain asthenospheric parental melt compositions, and 2) the well-exposed basaltic lavas have been divided into four different geochemical magma types that exhibit considerable trace element and radiogenic isotope heterogeneity (e.g., initial εNd from-16 to +2 at 180 Ma). We simulate the geochemical evolution of Vestfjella CFBs using 1) energy-constrained assimilation-fractional crystallization equations that account for heating and partial melting of crustal wallrock and 2)assimilation-fractional crystallization equations for lithospheric mantle contamination by using highly alkaline continental volcanic rocks (i.e. partial melts of mantle lithosphere) as contaminants. Calculations indicate that the different magma types can be produced by just minor (1–15 wt. %) contamination of asthenospheric parental magmas by melts from variable lithospheric reservoirs. Our models imply that the role of continental lithosphere as a CFB source component or contaminant may have been overestimated in many cases. Thus, CFBs may represent major juvenile crustal growth events rather than just recycling of old ...